A sala de cinema como espaço significante: o sentido do lugar - Kahtalian, Marcos (2022)
This research project aims to analyze the movie theater as a significant space for its audiences. The study justifies its relevance and falls within the framework of communicational studies, considering that, since the turn of the first decade of the 21st century, the attendance of movie theaters, its very existence, economic and symbolic importance has been losing its predominance in the activity of watching movies, in the face of new modes of appreciation. The hypothesis put forward is that the movie theater would not be a mere device among others to watch the film, but a device with a specificity that generates the most diverse effects of meaning, including ontological effects, since in a perspective of concrete social practice, going to the cinema would be confused with the meaning of the cinema object. The thesis is that the movie theater, due to its specificity, at the same time historical, but also transhistorical, would constitute a significant space, producer of signs, according to the audiences of its frequentation. To carry out this journey, classical and recent thinkers of cinema theories were mobilized, from the revisiting of the cinema situation by Hugo Mauerhofer, through the theories of the device of Jean-Louis Baudry, and other theorists who contribute to an interpretation of the phenomenon of cinema as a social fact. such as Edgar Morin; or those who focused on the ontological and epistemological consideration of the cinema object, such as Roland Barthes, Raymond Bellour, Jacques Aumont, André Gaudreault, Thomas Elsaesser, among others. In order to analyze the room as a significant space in itself, Peirce's semiotics will be mobilized; for the analysis of a specific case, special semiotics will be used. The thesis also presents, at the end, a specific case study, that of the exhibition group Estação, in Rio de Janeiro, emblematic in the formation of moviegoers in that city. For that, an analysis was carried out based on a qualitative interview and the evaluation of the group's trajectory; a semiotic study of a movie theater of the group was also carried out, in order to understand how meaning can be constructed by the expressive materials of the exhibition space and what kind of meanings can be elaborated for its audiences. It is believed that a political development of the research may be the evaluation of the place of cultural spaces in the city in a formative dimension that is significant for the formation of the symbolic capital of society